الصلابة النفسية لدى أمهات أطفال مرضى السرطان دراسة ميدانية في عيادة الشهيد قلومة ميلود الأغواط - دوة عائشة; بن رحمون ريحانة; سحيري زينب (My University, 2023)
The current study aims to find out the level of psychological hardiness among mothers of children with cancer patients, and for that, the clinical approach based on the case study method was relied upon, based on the semi-guided clinical interview with the aim of clinical observation based on the following questions: - What is the level of psychological hardness among mothers of children with cancer? Is there a relationship between psychological hardness and husband support? Is there a relationship between psychological hardness and the duration of the disease? Then, hypotheses were formulated on the basis of these questions. Imad Mukhaimer's measure of psychological hardness, which was codified by Bashir Maamaria, was applied. The results of the study revealed that the level of psychological hardness among mothers of children with cancer patients is low. There is no relationship between psychological hardness and husband support. There is no relationship between psychological hardness and the duration of the child's illness. Keywords: psychological hardiness, childhood cancer.